2010
DOI: 10.1097/nnr.0b013e3181dd25ef
|View full text |Cite
|
Sign up to set email alerts
|

Instrument Development Measuring Critical Care Nurses' Attitudes and Behaviors with End-of-life Care

Abstract: Background-Although critical care nurses are expected to focus on providing life-sustaining measures, many intensive care patients actually receive end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
2
27
0
1
Order By: Relevance
“…Personal experiences with PEOLC were found to influence students' knowledge, attitudes, and beliefs, which is consistent with previous research [11,30,39,40]. Students with personal experiences focused on the humanistic and holistic aspects of care.…”
Section: Influence Of Personal Experiencesupporting
confidence: 88%
“…Personal experiences with PEOLC were found to influence students' knowledge, attitudes, and beliefs, which is consistent with previous research [11,30,39,40]. Students with personal experiences focused on the humanistic and holistic aspects of care.…”
Section: Influence Of Personal Experiencesupporting
confidence: 88%
“…[15] At the onset of this project, 2009, a review of the literature was performed to identify existing tools evaluating evidence based practice in nursing. This search revealed 29 articles which described 17 different instruments.…”
Section: Tool Development and Validity Testingmentioning
confidence: 99%
“…To target this concern a new set of five industry and academic experts and five non-academics where asked to complete the electronic survey to specifically provide feedback on the useability of the interface and the comprehensibility of the survey items. Pilot testing an instrument for clarity and useability is a recognised strategy in the instrument development process (Zomorodi & Lynn, 2010). Feedback from these testers was generally positive with the instrument "easy to follow" and item wording "quite clear".…”
Section: Phase 1 (Stage 2) -Validation Of Mds-r (Aged Care)mentioning
confidence: 99%
“…Expert review is suggested as "the most convincing test of face validity…" (Gomm, 2008, p. 40), and is a strategy often used when designing measurement instruments (Curley, Hunsberger, & Harris, 2013;Ivankova, 2014;Kennerly et al, 2012;Kostovich, 2012;Zomorodi & Lynn, 2010). Face validity is concerned with determining through discussion that an individual measure represents the "…content of the concept"… it is intended to measure (Singh, 2007, p. 79).…”
Section: Phase 1 (Stage 1) -Instrument Amendmentmentioning
confidence: 99%
See 1 more Smart Citation